The lampshade kit with 8 ready-to-use lampshades and 8 pull-out patterns - St George, Amelia (Ebury Press, 1994)
This guide shows how to make classic and unusual lampshades from a range of materials, as well as providing eight pull-out, ready-to-use lampshades and eight pull-out tracings. There are also ideas for other original designs, using stencils and decoupage, textured papers and fabrics, card and embroidery. The book opens with instructions on how to make shades to fit any frame and in any material. Chapter by chapter, it then covers original ideas for using everything from stencils to needlepoint to make and decorate shades. Designs range from classic pleats, ribbons and bows, to more unusual cherub and star patterns. There are also ideas for creating special effects by using - stencil windows through light can shine or delicate tissue papers to cast a magical glow.